The Role of Teachers According to Ibn Jama'ah in the Book Tadhkirat al-Sami' wa'l-Mutakallim - Anwar, Saiful; Mustofa, Idam; Zarkasyi, Azmi (Lembaga Penelitian dan Pengabdian Masyarakat (LP2M) Sekolah Tinggi Ilmu Tarbiyah Muhammadiyah Tempurrejo Ngawi, 2024)
The book Tadhkirat al-Sami‘ wa’l-Mutakallim by Ibn Jama‘ah is a seminal work in the Islamic educational tradition, addressing the ethics and roles of teachers in the teaching process. This study aims to analyze the role of teachers as envisioned by Ibn Jama‘ah, focusing on the concepts of teachers as leaders of knowledge, ethical educators, and moral guides, while exploring its relevance to contemporary education. This research employs a library research method with a descriptive-analytical approach. The primary source is the book Tadhkirat al-Sami‘ wa’l-Mutakallim, complemented by secondary literature from books and academic journals. The analysis integrates classical and modern educational theories. The findings reveal that Ibn Jama‘ah regards teachers as central figures with significant responsibilities, not only in transferring knowledge but also in shaping students’ character through moral and spiritual example. These concepts, such as the importance of teachers' ethics and harmonious teacher-student relationships, remain relevant for character education in the modern era. The research implies the necessity of integrating moral and spiritual values into contemporary education to address global challenges such as ethical crises and dehumanization in educational systems. However, the study's focus on classical literature highlights the need for further empirical exploration to test its implementation in modern educational contexts. This study contributes to the literature on Islamic education by providing an in-depth analysis of Ibn Jama‘ah's concepts, which are rarely systematically addressed in contemporary research. The findings offer original insights bridging the tradition of classical Islamic education and the challenges of modern education.